THE EFFECT OF MANAGERIAL OWNERSHIP, WORKING CAPITAL MANAGEMENT, AND EXECUTIVE COMPENSATION ON COMPANY PROFITABILITY - Wardhani, Nurhastuty Kesumo; Junaedi, Daniel; Khomsiyah, Khomsiyah (JURNAL AKUNTANSI DAN AUDITING, 2023)
Several things that can impact the Profitability of a Company might be the size of the free cash flow, the managerial ownership structure, working capital management, and executive compensation. Once a Company has greater availability of free cash flow, the company has a greater ability to circulate the flow of money for the Company's operations in generating profits. The author’s purpose of research is to see the effect of managerial ownership structure, working capital management, and executive compensation on the profitability on manufacture Companies 'sub-sector chemicals listed on the Indonesia Stock Exchange from 2016 to 2020.Purposive sampling is the method being used by the Author, with the criteria of manufacturing Companies'sub-sector chemicals listed on the Indonesia Stock Exchange, which submitted consolidated financial statements from the year 2016-2020, the companies which earned profit from the year 2016-2020, rupiah currency and the company which listed from 2016-2020. The author decided to use dimensions of the days of sales inventory in this study in order to measure working capital management. The firm’s profitability is measured by Return On Assets. The analytical technique used is multiple linear regression. Keywords: Managerial Ownership, Working Capital Management, Executive Compensation, Free Cash Flow, Profitability